Pain as a predictor of frailty over time among older Mexican Americans - Sodhi, Jaspreet (Pain, 2020)
The objective of this study was to examine pain as a predictor of frailty over 18 years of follow-up among older Mexican Americans who were non-frail at baseline. Data were from a prospective cohort study of 1,545 community-dwelling Mexican Americans aged ≥67 years from the Hispanic Established Populations for the Epidemiological Study of the Elderly (1995/96 to 2012/13). Frailty was defined as meeting two or more of the following: unintentional weight loss of >10 pounds, weakness, self-reported exhaustion and slowness. The independent predictor was self-reported pain. Covariates included age, gender, marital status, education, comorbid conditions, body mass index, Mini Mental State Examination (MMSE), depressive symptoms and limitation in activities of daily living (ADLs). General Equation Estimation was performed to estimate the odds ratio of frailty as a function of pain. A total of 538 participants (34.8%) reported pain at baseline. The prevalence of frailty among those with pain ranged from 24.4% in wave 3 to 41% in wave 8. The odds ratio of becoming frail over time as a function of pain was 1.71; 95% Confidence Interval: 1.41–2.09 after controlling for all covariates. Older age, hip fracture, high depressive symptoms and ADL disability were also associated with higher odds of becoming frail over time. Female participants and those with higher levels of education and high MMSE scores were less at risk. In conclusion, pain was significantly associated with frailty. Early assessment and better management of pain may prevent early onset of frailty in older Mexican Americans.